DFT and Spectroscopy Studies of Zr (IV) Complexes Incorporating Amino Acids, 8-Hydroxyquinoline, and their Biological Activity - Abokhater, Rania Ahmad; Aldenfaria, Shafya.A.; Ashoor, Salem Eltuhami; Abdelrh, Suad Abdelgadir (European Journal of Applied Sciences, 2022)
The complexation of 8-hydroxyquinoline(HQ) and amino acids with zirconium(IV) chloride has been studied in aqueous solutions using UV/visible absorption, FT-IR spectroscopy accompanied by Density functional theory (DFT) calculations, Also they were characterized using elemental analysis, tandem mass spectrometry and X-ray powder diffraction (PXRD). Amino acids used in the study were (phal) phenylalanine, (His) Histidine, and (Try) Tryptophan as secondary ligands [Zr(HQ)(phal)]Cl2 (C1), [Zr(HQ)(His)]Cl2(C2), [Zr(HQ)(Try)]Cl2 (C3). Density Functional Theory (DFT) calculations have been carried out to investigate the e geometry of the coordination complex using the Gaussian 09 program. The molecular geometry was obtained from optimized using Density Functional Theory by using advanced calculations, CAM-Becke’s three parameters, Lee, Yang, and Parr approximation (DFT/CAM-B3LYP) method with the DGTZYP basis sets in the ground state. From the optimized geometry of the molecule, geometric parameters (bond lengths, and bond angles), and vibrational assignments of the title compounds have been calculated theoretically. Moreover, the new complexes were tested against the selected species of antibacterial types Staphylococcus-aureus , Streptococcus spp., Escherichia coli, Klebsiella spp., Psuedomones spp., and Protues spp.). The result revealed that the new compounds showed good efﬁcacy at high concentrations towards the growth inhibition of the selected pathogenic microorganism.